Optimized measurement methods and systems for the dielectric properties of active biological tissues in the 10Hz-100 MHz frequency range - Shi, Yueying; Bai, Xiaoxiao; Yang, Jingrong; Wu, Xinyu; Wang, Lei (Frontiers in Physiology, 2025)
The dielectric properties of active biological tissues within the 10Hz-100 MHz frequency range contain rich information about tissue morphology and function. Accurately understanding the dielectric properties of active human tissues holds significant value for disease diagnosis and electromagnetic protection. However, accurately measuring these properties has been challenging due to factors such as electrode polarization and distribution parameters. This study has developed a dual-purpose measuring cell that supports both four-electrode and two-electrode impedance measurements. Leveraging this development, we have established a system and methodology that is well-suited for the dielectric property measurement of active biological tissues within the frequency range of 10Hz to 100 MHz. Our measurements of dielectric properties in NaCl solutions of varying concentrations and pig liver tissues demonstrate the system’s high accuracy and repeatability. For NaCl solutions, the maximum relative deviation is only 6.34%, with an average deviation of less than 1.5%. For pig liver tissues, the overall relative deviation is below 6%. Through the integration of the four-electrode and two-electrode measurement systems, we have successfully addressed the challenges of electrode polarization at low frequencies and the influence of distribution parameters at high frequencies, achieving a significant improvement in measurement accuracy across the spectrum.